Linguistic and Culturological Analysis Of Caricature Texts - M A Belova; V M Shaklein (Russian Language Studies, 2012)
The article is devoted to actual problems of studying caricature texts. The article deals with theoretical and methodical issues of making annotations to those texts; we also analyse the notion linguistic cultureme in linguistic culturology as the unit with linguistic and cultural meaning and its functioning in Russian caricatures.